2021
DOI: 10.5194/acp-21-7695-2021
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric gravity waves over the mountainous island of South Georgia: testing a high-resolution dynamical model with 3-D satellite observations and radiosondes

Abstract: Abstract. Atmospheric gravity waves (GWs) play an important role in atmospheric dynamics but accurately representing them in general circulation models (GCMs) is challenging. This is especially true for orographic GWs generated by wind flow over small mountainous islands in the Southern Ocean. Currently, these islands lie in the “grey zone” of global model resolution, where they are neither fully resolved nor fully parameterised. It is expected that as GCMs approach the spatial resolution of current high-resol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 93 publications
1
29
0
Order By: Relevance
“…Opposite or different phases between the model and AIRS results have also been shown in a recent paper by Hindley et al. (2020) who investigated GW events during the wintertime in the region of the island of South Georgia using a regional model with very high resolution and driven by reanalysis at its lateral boundaries. Also note that the HIAMCM shows medium‐scale GWs in the stratosphere over northern Europe at 33 km (Figure 8a) and at lower altitudes (Figures 8d and 8e) that are neither captured by MERRA‐2 nor by AIRS.…”
Section: Comparison Of Simulated Stratospheric Gw Events In January 2...supporting
confidence: 62%
“…Opposite or different phases between the model and AIRS results have also been shown in a recent paper by Hindley et al. (2020) who investigated GW events during the wintertime in the region of the island of South Georgia using a regional model with very high resolution and driven by reanalysis at its lateral boundaries. Also note that the HIAMCM shows medium‐scale GWs in the stratosphere over northern Europe at 33 km (Figure 8a) and at lower altitudes (Figures 8d and 8e) that are neither captured by MERRA‐2 nor by AIRS.…”
Section: Comparison Of Simulated Stratospheric Gw Events In January 2...supporting
confidence: 62%
“…It is expected from recent studies (e.g. Wright et al, 2017;Hindley et al, 2019Hindley et al, , 2020Hindley et al, , 2021 that the stratosphere exhibits a strong westward tendency in GW momentum flux over the Southern Ocean during winter for upwardly propagating GWs. If these westward GWs propagate up to the mesosphere, we would expect to see a strong zonal directional tendency in Fig.…”
Section: Gw Directionsmentioning
confidence: 94%
“…In a recent numerical modelling study over South Georgia, Hindley et al (2021) found that in some cases, mountain waves from South Georgia can reach altitudes near the stratopause at around 75 km if eastward wind conditions were favourable throughout the stratosphere. In one example (their Sect.…”
Section: Gw Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A means of validating the parametrization scheme directly across a range of grid spacings is therefore required. Gravity waves simulated using high‐resolution simulations have been shown to agree well with satellite‐derived observations, in terms of timing and amplitude (Hindley et al ., 2020), and they provide a dataset for validating parametrization schemes that is sampled uniformly in both space and time. Here, we exploit the seamless modelling framework of the Met Office Unified Model by performing simulations, both regional and global, at horizontal grid spacings ranging from 2–130 km.…”
Section: Introductionmentioning
confidence: 99%